TASK SCHEDULING AUTOMATION AND ORGANISATIONAL EFFICIENCY: STUDY OF SELECTED FIRMS IN OGUN – STATE NIGERIA - Comfort E., Omorogbe; Johnson B., Odumosu (International Journal For Research In Business, Management And Accounting, 2017)
Task scheduling automation was examined to provide evidence on its effect on organsational efficiency by reference to two fully automated firms in Ogun State of Nigeria. Organisational efficiency was measured in terms of individual’s commitment to work, productivity, quality output and workflow efficiency. A structured questionnaire was administered to 56 employees from both firms. The inferential statistical tool, specifically the regression analysis measured the effect of automated task scheduling on workflow efficiency and whether individual commitment and productivity increased with the use of time tracking software. The result revealed that task scheduling had a significant effect on workflow efficiency. Task scheduling explained about 33.9% (R2 = 0.339) variation of workflow efficiency; and time tracking software’s ability to impel increase in employees’ commitment to work was not significant (p< 0.01). It was recommended that task scheduling should be considered by firms as it gives employees a clearer insight into organisation’s objectives and assist firms in meeting with daily tasks, urgent orders and deadlines. Additionally, time tracking software would permit task and time monitoring in such a way that employees time are judiciously utilised for organisational efficiency.